Treatment planning comparison in the PROTECT-trial randomising proton versus photon beam therapy in oesophageal cancer: Results from eight European centres. (July 2022) - Hoffmann, Lone; Mortensen, Hanna; Shamshad, Muhammad; Berbee, Maaike; Bizzocchi, Nicola; Bütof, Rebecca; Canters, Richard; Defraene, Gilles; Ehmsen, Mai Lykkegaard; Fiorini, Francesca; Haustermans, Karin; Hulley, Ryan; et al.
Highlights: Large variability in dose to OAR between 8 centres comparing photon and proton plans. Anatomical changes may result in large under-dosage and require adaptation. Inter-fractional changes led to larger target under-dosage than respiratory motion. Robustness towards anatomical changes differs between proton and photon therapy. Robustness towards anatomical changes differs between centres. Abstract: Purpose: To compare dose distributions and robustness in treatment plans from eight European centres in preparation for the European randomized phase-III PROTECT-trial investigating the effect of proton therapy (PT) versus photon therapy (XT) for oesophageal cancer. Materials and methods: All centres optimized one PT and one XT nominal plan using delineated 4DCT scans for four patients receiving 50.4 Gy (RBE) in 28 fractions. Target volume receiving 95% of prescribed dose (V95%iCTVtotal ) should be >99%. Robustness towards setup, range, and respiration was evaluated. The plans were recalculated on a surveillance 4DCT (sCT) acquired at fraction ten and robustness evaluation was performed to evaluate the effect of respiration and inter-fractional anatomical changes. Results: All PT and XT plans complied with V95%iCTVtotal >99% for the nominal plan and V95%iCTVtotal >97% for all respiratory and robustness scenarios. Lung and heart dose varied considerably between centres for both modalities. The difference in mean lung dose and mean heart dose between each pair of XT and PT plans was in median [range] 4.8 Gy [1.1;7.6] and 8.4 Gy [1.9;24.5], respectively. Patients B and C showed large inter-fractional anatomical changes on sCT. For patient B, the minimum V95%iCTVtotal in the worst-case robustness scenario was 45% and 94% for XT and PT, respectively. For patient C, the minimum V95%iCTVtotal was 57% and 72% for XT and PT, respectively. Patient A and D showed minor inter-fractional changes and the minimum V95%iCTVtotal was >85%. Conclusion: Large variability in dose to the lungs and heart was observed for both modalities. Inter-fractional anatomical changes led to larger target dose deterioration for XT than PT plans.